(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
The use of technology in second language vocabulary instruction has moved through several distinct paradigms over the past six decades, from early computer assisted drills to today’s mobile applications capable of delivering personalized, spaced, and context-aware vocabulary practice. This review traces that trajectory, situating the historical phases of computer-assisted language learning (CALL) identified by Warschauer (1996) and reconceptualized by Bax (2003) alongside the emergence of mobile-assisted language learning (MALL) as a distinct field with its own theoretical concerns around mobility, personalization, and the blurring of formal and informal learning contexts (Kukulska-Hulme, 2009; Kukulska-Hulme & Shield, 2008). Particular attention is given to vocabulary instruction specifically, an area where the shift from desktop-based CALL to mobile-based MALL has been both theoretically significant and empirically mixed, given early findings that mobile platforms did not consistently outperform desktop computers for vocabulary tasks (Stockwell, 2007, 2010). The review concludes by identifying persistent gaps in the literature, including the need for more classroom-based, non-Western, and secondary level research on mobile vocabulary instruction, and reflects on where the field appears to be heading as applications mature beyond simple digitized flashcards.